FRI0070 Safety and tolerability of a rapid infusion of remicade (infliximab) in the treatment of rheumatoid arthritis. (1st June 2001) - Isern, RA; Sanders, C; Hughes, G; Toder, S; Keenan, G
Abstract : Background: The safety of infliximab has been established in both open-label and randomised controlled clinical trials in which patients received infliximab over 2 hrs. In clinical trials, no difference was observed in the incidence of infusion reactions at any infliximab dose between 3 and 10 mg/kg given over 2 h. This clinical experience supported the safety of administering infliximab 3 mg/kg over 1 hr (Maini, 1999). Current guidelines advise infusing infliximab over at least 2 h. Objectives: To determine if infliximab given at 3 mg/kg over 1 hr is safe and well tolerated in the clinic setting. Methods: Patients with active RA enrolled at selected sites in an ongoing open-label clinical trial of infliximab were eligible to receive two open-label 1-hr infusions of infliximab 3 mg/kg if they had previously tolerated four 2-hr infusions (at Weeks 0, 2, 6, and 14) without any moderate to severe infusion related reactions or hypersensitivity reactions and had no significant history of cardiac or renal impairment. Safety evaluations included measurements of vital signs during and immediately after the infusions of infliximab and assessment for adverse events. Results: One hundred ninety patients (76% women and 24% men) received infliximab 3 mg/kg given over 1 hr. Patients ranged in age from 26 to 82 yrs (mean of 59.4 yrs). Twelve (6%) patients reported adverse events associated with the first or second 1-hr infusion of infliximab. Headache, hypersensitivity, and hypertension were each reported by two (1%) patients. The following adverse reactions were reported by one (0.5%) patient each: anaphylactic reaction, blood pressure decreased, chest tightness, dizziness, itching, maculopapular rash, and somnolence. Only 3 patients discontinued infliximab therapy as a result of an infusion-related reaction (1 with anaphylactic reaction and 2 with allergic reaction). All reactions, which were generally mild or moderate in nature, resolved within 1 day of onset. Conclusion: Infliximab 3 mg/kg administered over 1 hr was well tolerated by these patients with active RA. Reference: Maini RN, St. Clair EW, Maini RN, et al . Infliximab (chimeric anti-tumour necrosis factor alpha monoclonal antibody) versus placebo in rheumatoid arthritis patients receiving concomitant methotrexate: a randomised phase III trial. Lancet 1999;354:1032–1939